2015
DOI: 10.2105/ajph.2014.302393
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying Perpetration and Victimization Among Middle-School Students

Abstract: Cyberbullying interventions should account for gender and sexual identity, as well as the possible benefits of educational interventions for intensive Internet users and frequent texters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(90 citation statements)
references
References 16 publications
7
76
1
6
Order By: Relevance
“…The three high-quality studies reported prevalence in the last couple of months of 2.3% 39 and in the last year, 3% and 4.5%. 41,52 …”
Section: Resultsmentioning
confidence: 99%
“…The three high-quality studies reported prevalence in the last couple of months of 2.3% 39 and in the last year, 3% and 4.5%. 41,52 …”
Section: Resultsmentioning
confidence: 99%
“…According to some studies, girls are more engaged in cyberbullying (Agastson et al, 2007;Campfield, 2008;Rivers & Noret, 2010;Slonje & Smith, 2008;Wolak, Mitchell, & Finkelhor, 2007) or to be exposed cyberbullying than boys (Akbaba & Ero glu, 2013;Dehue, Bollman, & V€ ollink, 2008;Dempsey, Sulkowski, Nichols, & Storch, 2009;Heirman & Shemesh, 2015;Papatraianou, Levine, & West, 2014;Rice et al, 2015;Vandebosch & VanCleemput, 2009). Moreover, there are some studies that show that girl students make more cyberbullying and they are more exposed to cyberbullying (Campbell, 2005;Kowalski & Limber, 2007;Li, 2007;Smith et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rice et al (2015), Papatraianou et al (2014), Heirman andShemesh (2015), Akbaba and Ero glu (2013), Campfield (2006), Dempsey et al (2009), Li (2010), and Mesch (2009 state that females are more exposed to cyberbullying than males. On the other hand, Uysal et al (2014), Balakrishnan (2015), Baroncelli and Ciucci (2014), Ozdemir and Akar (2011), Li (2006), Slonje and Smith (2008) found that there is no significant difference between males and females for cybervictimization which is consistent with the findings of the current research.…”
Section: The Relationship Between Gender and Cyberbullying And Cybervmentioning
confidence: 99%
“…In this context, knowing cyber bullying and related variables is anxiety as important and valuable for eliminating or at least minimizing the negative behaviors. In conducted literatüre review it is seen that cyber bullying associated with different variables such as daily internet usage time, parents' educational levels, subjective well-being, parental control, sense of belonging to school, perceived academic success, gender, (Akbaba & Eroğlu, 2013;Navarro, Ruiz-Oliva, Larrañaga, & Yubero, 2015;Peker, Eroğlu & Ada, 2012;Rice et al , 2015;Wong, Chan & Cheng, 2014) as well as associated with social variables such as empathy, interpersonal sensitivity, perceived social support. Batman & Ayas 2013; Peker & Eroğlu, 2015;Rey, Lazuras, Casas, Barkoukis, Ruiz, & Tsorbatzoudis, 2016).…”
Section: Discussionmentioning
confidence: 99%